KESADARAN KEBANGSAAN PADA SETIAP TAHAPAN PERJALANAN KEBANGSAAN INDONESIA - Monalisa Martha Siahaan (Ensiklopedia Education Review, 2021)
The function of education is the transformation of culture and values to students, so that they are able to understand, internalize and convey to the next generation. One of them is character education. Of course, character education will be very good if it is supported by other sciences. This article is supported by psychology. The research method used in this article is a literature review research method or literature study, which contains relevant theories. The conclusion of this article states that character education shapes one's personality through character education, the results of which can be seen in one's real actions, namely good behavior, honest responsibility, respect for others, hard work, and so on. Character education is supported by educational psychology. Educational psychology is more of a science that can be applied in everyday life, especially about how our society manages learning. Educational Psychology has developed into a science that focuses on the discovery and application of psychological principles and techniques into education, so the scope of educational psychology covers topics that are closely related to character education. The purpose of character education is very good to use and develop. Content, methods in the form of implementation, methods in the form of guarding, educational tools in the form of action, character education environment, as well as students, both to be used and developed supported by other sciences apart from psychology.Keywords: National Awareness, Journey Stages, Nationality, Indonesia